METHODS OF EFFECTIVE USING OF SPEAKING COMPETENCE IN THE ORGANIZATION OF TEACHING FOREIGN LANGUAGE IN TECHNICAL HIGHER EDUCATIONAL INSTITUTIONS (Scientific journal of the Fergana State University, 2023)
The article is devoted to the demand for teaching and learning. Monitoring new knowledge and relationships in students is the task of every foreign language teacher and every teacher. The main goal of teaching a foreign language to students is to acquire basic speech structures corresponding to the level of speech competence. Teaching communicative competence is based on topics that meet the real needs and interests of students.